The only grant-writing book you'll ever need - Karsh, Ellen; Fox, Arlen Sue (Basic Books, 2019)
Written by two expert authors who have won secured millions of dollars in government and foundation grants, The Only Grant-Writing Book You'll Ever Need is the classic book on grant seeking, providing a comprehensive, step-by-step guide for government, nonprofit, and individual grant seekers. Drawing on decades of experience in grant writing and professional development, Ellen Karsh and Arlen Sue Fox demystify the process of securing grants while offering indispensable advice from funders and recipients. --